Malnutrition-Inflammation complex syndrome in Libyan patients with end-Stage renal disease at Hun-Aljufrah - Mulah, Mohammed; Zaed , Hana (Libyan Journal of Science &Technology, 2022)
Malnutrition and inflammation complex syndrome in ESRD Patients on maintenance Hemodialysis therapy remains the most common cause of morbidity and mortality characterized by alteration in the structural and functional ability of plasma proteins. The aim of this study was to assess the serum level of albumin, BMI and hs-CRP as a marker of Malnutrition-Inflammation Complex Syndrome. This is a case-control study conducted at Alafia Hospital Hun-Aljufrah from December 2014 to December 2015. Libyan patients with ESRD who routinely attend to dialysis center at the above-mentioned hospital during the period of the study were randomly recruited for this study. The study included one hundred ESRD and one hundred age and sexmatched healthy controls. The patients’ information such as age, sex, height, weight, and clinical history were recorded. Blood samples (6 ml) were collected from patients in plain and EDTA containers from which EDTA and Serum samples were separated. The results of our study showed that there were significant decrease in the mean serum level of albumin (3.12±0.39) (p. value=0.000) and BMI (20.3±5.5) (p. value=0.000) as well as significant increase in the mean serum level of serum C-reactive protein (20.13±5.704) (p. value=0.000) in case group when compared to the control group. The DOT Blot Correlation test showed that there was a significant negative correlation between hs-CRP with albumin (r= -0.812, p=0.02). In conclusion, the significant decreased in the mean level of serum albumin and BMI, as well as the significant increase in the mean level of serum C-reactive protein among hemodialysis ESRD patients, might place them at risk of developing Malnutrition-Inflammation Complex Syndrome in the future. The significant negative correlation between serum albumin with hsCRP support the facts systemic inflammation is the main cause of malnutrition and cardiovascular disease in ESRD patient.